2022
DOI: 10.5888/pcd19.210343
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wrist- and Hip-Worn Activity Monitors When Meeting Step Guidelines

Abstract: What is known on this topic? People commonly use wristband physical activity (PA) monitors to measure steps taken per day so they can accumulate the recommended 10,000 steps. However, wristband PA monitors may not be as accurate in determining the number of steps as validated, hip-worn pedometers.What is added by this report?We compared the difference between number of steps taken measured using both wrist-worn and hip-worn PA monitors and found significant differences between devices as well as meaningful dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Many previous studies have demonstrated that the waist-worn pedometers have higher accuracy and underestimated the number of steps compared to the wrist-worn pedometer during walking 15,19,20 , which aligns with our observations. For instance, one study reported that the wrist-worn pedometers underestimated the number of steps by 2.7 to 10.2%, whereas the waist-worn pedometers presented only a -0.4% underestimation during 5 minutes of walking 15 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Many previous studies have demonstrated that the waist-worn pedometers have higher accuracy and underestimated the number of steps compared to the wrist-worn pedometer during walking 15,19,20 , which aligns with our observations. For instance, one study reported that the wrist-worn pedometers underestimated the number of steps by 2.7 to 10.2%, whereas the waist-worn pedometers presented only a -0.4% underestimation during 5 minutes of walking 15 .…”
Section: Discussionsupporting
confidence: 92%
“…Compared to the wrist-worn pedometers, the waist-worn pedometers have higher accuracy in estimating steps during activities 15,[17][18][19][20] . For example, a study observed that the waist-worn pedometers underestimated steps by only 0.4% for a ve-minute walk 15 .…”
Section: Introductionmentioning
confidence: 99%
“…While commercial wearable activity trackers are limited by proprietary summaries of the data, often provided at a daily or hourly level, smartphones offer an opportunity to access raw sub-second level data which can be used to generate reproducible and interpretable digital biomarkers, such as step counts, with research software. Moreover, smartphones are typically carried close to the center of the body, which produces less noisy inertial sensor data compared with the locations that many available wearables are worn (i.e., on the wrist), which provides more accurate estimations of whole-body motion (18,19,(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Using activities of daily living, previous analyses have shown that estimates of step count were ~1200 steps/day higher when derived from consumer-grade wrist-worn devices. compared with a pedometer worn at the waist [34,35] and direct observation [36]. When comparing ActiGraph accelerometers worn synonymously on the waist and wrist during 7 days of free-living, Tudor-Locke et al [37] reported the device worn on the wrist estimated 2500 more steps/day compared with that on the waist.…”
Section: Discussionmentioning
confidence: 99%